Defining the Concept of Wavelength in SME relationships with non‐consulting business support services. - Cresswell, Sarah (2011)
In recent research SME owners sited trust as the predominant blockage to commissioning external professional support (Cresswell and Preece, SME Interviews 2011). However little academic research has been conducted on the subject of trust and the SME sector. Research relating to trust and corporation’s sites ‘wavelength’ as an essential component of trust, however little clarification of the definition and components of wavelength can be found. Therefore research is required to determine the definition and constituent parts of wavelength, as they are perceived by the SME sector in order to establish its importance to the commissioning of non-consulting professional services.